Analisis Dampak Bermain Game Mobile Legends Terhadap Perilaku Toxic Anak-Anak Hingga Dewasa - Bachtiar Rizky Alamsyah; Ananda Surya Dahana Dewantara; Daffa Maheswara Iswidono; Noval Rizqi Santoso; Nur Aini Rakhmawati (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to analyze the impact of playing Mobile Legends on toxic behavior in both children and adults. The background of this study is based on the fact that Mobile Legends is one of the popular online games in Indonesia and is widely played by children to adults, often exhibiting toxic behaviors. The method used in this research is a survey. The results of the study indicate that out of 15 survey questions, 90% of the respondents showed a tendency towards toxic activities while playing Mobile Legends. This indicates that individuals ranging from children to adults often engage in toxic behavior, such as using offensive language during gameplay. Therefore, one of the recommendations to create a healthier gaming environment is to block such accounts to prevent them from playing the game for a certain period.